Enterprise digital transformation, managerial myopia and cost stickiness - Yu Li; Panpan Feng; Tiange Qi; Jiale Yan; Yongjian Huang (Humanities & Social Sciences Communications)
Abstract Using Chinese-listed enterprise data from 2010 to 2021, we study the relationships among enterprise digital transformation, managerial myopia and cost stickiness. The results show that enterprise digital transformation inhibits cost stickiness, including operating cost stickiness as well as selling, general and administrative (SG&A) cost stickiness. This result holds after various robustness and endogeneity tests. Additionally, mechanism research indicates that enterprise digital transformation inhibits cost stickiness by reducing adjustment costs (ACs) and alleviating financing constraints (SAs). However, managerial myopia negatively affects the inhibition of enterprise digital transformation on cost stickiness by increasing ACs and aggravating SAs. Furthermore, the relationship between enterprise digital transformation and cost stickiness is stronger for mature, state-owned and high-tech enterprises than for those with better digital economy policy environments.